The lipid linked oligosaccharide polymerase Wzy and its regulating co-polymerase, Wzz, from enterobacterial common antigen biosynthesis form a complex - Miriam Weckener; Laura S. Woodward; Bradley R. Clarke; Huanting Liu; Philip N. Ward; Audrey Le Bas; David Bhella; Chris Whitfield; James H. Naismith (Open Biology, 2023)
The enterobacterial common antigen (ECA) is a carbohydrate polymer that is associated with the cell envelope in the Enterobacteriaceae. ECA contains a repeating trisaccharide which is polymerized by WzyE, a member of the Wzy membrane protein polymerase superfamily. WzyE activity is regulated by a membrane protein polysaccharide co-polymerase, WzzE. Förster resonance energy transfer experiments demonstrate that WzyE and WzzE from Pectobacterium atrosepticum form a complex in vivo, and immunoblotting and cryo-electron microscopy (cryo-EM) analysis confirm a defined stoichiometry of approximately eight WzzE to one WzyE. Low-resolution cryo-EM reconstructions of the complex, aided by an antibody recognizing the C-terminus of WzyE, reveals WzyE sits in the central membrane lumen formed by the octameric arrangement of the transmembrane helices of WzzE. The pairing of Wzy and Wzz is found in polymerization systems for other bacterial polymers, including lipopolysaccharide O-antigens and capsular polysaccharides. The data provide new structural insight into a conserved mechanism for regulating polysaccharide chain length in bacteria.